PO 8458 Polymorphism of the plasmodium falciparum msp-2 gene associated with placental malaria at the borgou-alibori departmental hospital. (24th April 2019) - Akpéyédjé, Dossou; Issifou, Saadou
Abstract : Background: In sub-Saharan Africa, malaria during pregnancy is a major health problem because it poses significant risks for the pregnant woman and the foetus. The sequestration of Plasmodium falciparum -infected erythrocytes in the placenta has consequences for the mother and the foetus. This study aimed to evaluate the allelic polymorphism of the Plasmodium falciparum MSP-2 gene related to the consequences of placental malaria. Methods: It was a cross-sectional study conducted over two periods lasting six months in 2016 and 2017. The maternity center of the Hospital of Borgou-Alibori in Benin served as a framework for the study. From the 98 parturients included, placental blood samples were taken and then genotyped. Results: Using the MSP-2 gene as marker, the prevalence was 17,  34%. The MSP-2 gene was polymorphic with 9 distinct allelic types for both 3D7 and FC27 families (150 bp; 200 bp; 250 bp; 275 bp; 300 bp; 350 bp; 400 bp; 450 bp and 500 bp). The FC27 allelic family was predominant over the 3D7 family with 56, 25% and 43,  75% respectively. The 300 bp allelic type (50%) was predominant in the FC27 family while the 400 bp type was predominant in 3D7 family (35, 71%). 9 women had polyclonality (52, 94%). The multiplicity of infection (MOI) was 1, 88. The number of strains ranged 1 to 4 in infected women. In univariate analysis there was no significant relationship between MSP-2 gene polymorphism and maternofoetal consequences. The absence of prenatal consultation (p=0.0270), non-taking of IPTp/SP (p=0.0060), the occurrence of malaria in the third trimester (p=0, 0364) and moderate maternal anaemia (p=0.0277) were associated with the polymorphism of MSP-2 gene. The MOI was significantly associated with parasite density of infected women. Conclusion: Plasmodium falciparum MSP-2 gene was polymorphic in infected women at Parakou. Several factors related to pregnancy monitoring were associated with this genetic diversity. It is therefore essential to ensure correct follow-up of pregnancies.